MENGGUNAKAN CODE-SWITCHING SEBAGAI STRATEGI PEMBELAJARAN PADA SISWA KELAS IV SEKOLAH DASAR INDONESIA DI KELAS BUDAYA INDONESIA - FATHIA ANGGRIANI PRADINA (Universitas Trilogi, 2022)
The Indonesian 4th-grade students’ conversations are considered the code-switchingphenomenon because when they try to show their strategy in learning the subject at school, the Indonesian 4th-grade students switch from their first language to English. Their first language refers to Indonesian language. The paper aims to analyze and describe the function of code-switching to English used by Indonesian 4th-grade students in their conversations. The method used in this research is a descriptive analysis. The present writer collects, classifies, and analyzes the data based on the theories used in this research. The result shows that code-switching in Indonesian 4th-grade students' conversations affects several factors. They are topic, and function, or goal. This phenomenon shows that code-switching can be very useful as one of the tools in learning strategy for students who have the ability in speaking more than one language. Code-switching helps the students to understand the subject better and leaves no misunderstanding.